REDESIGN PAKAIAN SECONDHAND BERWARNA PUTIH MENGGUNAKAN TEKNIK SURFACE TEXTILE DESIGN DENGAN INSPIRASI KEMBANG KELAPA - Destia Fani Maghfira; Arini Arumsari (Jurusan Seni Rupa ISBI Bandung, 2020)
The world fashion industry is currently developing so rapidly with the addition of various types of clothing products that make it more abundant secondhand clothing. In Indonesia, there is a secondhand clothing sales center, one of which is Cimol Gede Bage Market, which is a place to accommodate secondhand clothes that are still suitable for use. According to the field survey conducted by the author, 65% of the shops located in Cimol Gede Bage Market sell white clothes. The author sees the potential of the white secondhand clothing that allows the existence of defects in the form of stains to become a new product. This research uses a qualitative method in which the data collection is through literature study, observation, interview and exploration to find out the optimal technique to be applied to clothing products to be processed. The purpose of this study is to increase the value of function, economy, and can increase the life span of the product. By using the upcycle redesign method on white secondhand clothing, increasing the aesthetic value of secondhand clothing products will be processed using a number of surface textile design techniques inspired by Coconut Flower which come from Betawi Regional Art.Keywords: Secondhand white clothes, Redesign, Cimol Gede Bage Market, Coconut Flower.____________________________________________________________________Dunia industri fashion saat ini berkembang begitu pesat dengan penambahan berbagai jenis produk pakaian yang membuatnya semakin melimpah pada pakaian bekas. Di Indonesia sendiri terdapat sentra penjualan pakaian bekas salah satunya Pasar Cimol Gede Bage yang merupakan tempat menampung pakaian bekas yang masih layak pakai. Menurut survey lapangan yang dilakukan penulis, 65% toko yang berada di Pasar Cimol Gede Bage menjual pakaian putih. Penulis melihat potensi pakaian bekas berwarna putih yang memungkinkan adanya cacat berupa noda menjadi produk baru. Penelitian ini menggunakan metode kualitatif dimana pengumpulan datanya melalui studi pustaka, observasi, wawancara dan eksplorasi untuk mengetahui teknik yang optimal untuk diterapkan pada produk sandang yang akan diolah. Tujuan dari penelitian ini adalah untuk meningkatkan nilai fungsi, keekonomisan, dan dapat meningkatkan umur produk. Dengan menggunakan metode redesain upcycle pada pakaian bekas berwarna putih maka akan meningkatkan nilai estetika produk pakaian bekas yang akan diolah dengan menggunakan sejumlah teknik desain tekstil permukaan yang terinspirasi dari Bunga Kelapa yang berasal dari Kesenian Daerah Betawi.Kata kunci: baju bekas putih, desain ulang, Pasar Cimol Gede Bage, Bunga Kelapa.